The Effect of Credit Risk And Efficiency on Bank Performance in Indonesian Banking: With Liquidity as A Mediation Variable - Nursyirwan, Vivi Iswanti; Dewi, Melina Sari (EAJ (Economic and Accounting Journal), 2021)
Bank performance is important in the stability of a country. If a bank's financial performance is poor, it will have an impact on channeling funds to who need funds and will hinder the economy of a country. Therefore, this research was conducted to examine the factors that influence bank performance. This research has developed novelty that is of from research before with the use of an intermediary variable is Liquidity. This research uses secondary data in the form quarter time series from 2013 to 2019. The population and samples in this study are 41 conventional banks. The sampling technique used is exhaustive sampling method. The data analysis technique used is Path Analysis and Sobel Test to measure Intervening variables. The results of research on substructure I that partially Credit Risk and Efficiency have a negative and significant effect on Bank Performance, while the level of Liquidity has no effect on Bank Performance. In substructure II, Credit Risk and Efficiency do not affect the Liquidity Level. For the path analyze results in this research using the single test, it is found that the liquidity level does not interfere in the effect of credit and efficiency on bank performance.